The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/chem.200500187
|View full text |Cite
|
Sign up to set email alerts
|

Induced Axial Chirality in the Biphenyl Core of the Proatropoisomeric, Cα‐Tetrasubstituted α‐Amino Acid Residue Bip in Peptides

Abstract: An induced axial chirality in the biphenyl core of the 2',1':1,2;1'',2'':3,4-dibenzcyclohepta-1,3-diene-6-amino-6-carboxylic acid (Bip) residue, a conformationally labile, atropoisomeric, C(alpha)-tetrasubstituted alpha-amino acid, was observed by CD and (1)H NMR spectroscopic techniques in the linear dipeptides Boc-Bip-Xaa*-OMe where Boc=tert-butoxycarbonyl, OMe=methoxy, and Xaa*=D- and/or L-Ala, -Val, -Leu, -Phe, -(alphaMe)Val and -(alphaMe)Leu. Chiral induction was significantly lower in the isomeric dipept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 37 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…Peptides based on Bin and Bip show a clear tendency for β‐turn and 3 10 ‐helical structures, although in short peptides the fully extended conformation would also be populated to some extent.…”
Section: Axial Chiralitymentioning
confidence: 99%
See 2 more Smart Citations
“…Peptides based on Bin and Bip show a clear tendency for β‐turn and 3 10 ‐helical structures, although in short peptides the fully extended conformation would also be populated to some extent.…”
Section: Axial Chiralitymentioning
confidence: 99%
“…A relationship between axial chirality, side‐chain torsion angles and helical screw‐sense identical to that of Bin can be derived from the crystal structures of Bip peptides and derivatives, in which ( S )‐Bip is always left‐handed helical and ( R )‐Bip right‐handed helical. In solution, however, at variance with Bin, the ( S ) and ( R ) enantiomers of Bip can interconvert.…”
Section: Axial Chiralitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Usually, such atropisomeric systems are required to be configurationally stable at the reaction temperature because configurationally flexible biaryls undergo rapid racemization, which makes them unable to transfer any chiral information. The latter approach shows a more general character, and it has been applied as both a method of chirality detection, developing flexible biphenyl probes for absolute configuration assignment via electronic circular dichroism (ECD) spectroscopy, [3,4] and as a source of chirality induction, allowing numerous efficient chiral ligands that are employed in asymmetric catalysis devel-oped. Such central-to axial-chirality transfer can occur through both noncovalent and covalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The development of conformationally flexible receptors capable of reporting a molecular recognition event upon binding to a substrate provides new avenues for chiroptical analysis . For example, Rosini and Toniolo demonstrated that the absolute configuration of chiral amino acids, carboxylic acids, and alcohols can be correlated to the ICD output of a covalently linked stereodynamic biphenyl reporter unit . The same principles have been exploited with molecular bevel gears, propellers, and other well‐defined arrangements .…”
Section: Introductionmentioning
confidence: 99%